Ekonomska teorija in ex ante regulacija - Ferčič, Aleš (LeXonomica, 2020)
Economic theory and ex ante regulation. In this article the author deals with the question in which cases the state or its competent regulatory body should perform ex ante regulation on ’liberalized’ infrastructure markets. The author for this purpose applies economic theory as an instrument for assessing merits of ex ante regulation. The author in this regard ascertains that ex ante regulation means intensive public authority intervention on the market, which should be applied only exceptionally in a market economy. A typical example when ex ante regulation should be performed, is the so called bottleneck situation, i. e., a situation when two cumulative conditions are met. Namely, when there is an infrastructure indispensable for business activities on the downstream market but there is no active substitute because of a natural monopoly effect, and when there is no potential substitute that would discipline the owner of the sole infrastructure because of sunk costs. Povzetek. V tem članku se avtor ukvarja z vprašanjem, v katerih primerih naj država oziroma njena pristojna regulatorna telesa na "liberaliziranih" infrastrukturnih trgih vršijo ex ante regulacijo. V ta namen uporablja ekonomsko teorijo kot instrument za presojo utemeljenosti ex ante regulacije. Avtor v tej zvezi ugotavlja, da je ex ante regulacija intenzivno oblastno poseganje na trg, ki se v tržnem gospodarstvu uporablja le izjemoma. Tipičen primer, ko naj se vrši ex ante regulacija, je t. i. položaj "ozkega grla", položaj, ko sta kumulativno izpolnjena dva pogoja, in sicer ko gre za infrastrukturo, ki je neophodna za poslovanje oz. delovanje podjetja na spodnjem, vertikalno povezanem trgu, vendar zaradi učinka naravnega monopola ne obstaja dejanski substitut, in ko zaradi učinka nepovratnih oz. ireverzibilnih stroškov ne obstaja potencialen substitut, ki bi discipliniral lastnika oziroma imetnika edine infrastrukture.